Oropharyngeal cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Mehanna, H; Evans, M; Beasley, M; Chatterjee, S; Dilkes, M; Homer, J; O'Hara, J; Robinson, M; Shaw, R; Sloan, P
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. There has been significant debate in the management of oropharyngeal cancer in the last decade, especially in light of the increased incidence, clarity on the role of the human papilloma virus in this disease and the treatment responsiveness of the human papilloma virus positive cancers. This paper discusses the evidence base pertaining to the management of oropharyngeal cancer and provides recommendations on management for this group of patients receiving cancer care. Recommendations: Cross-sectional imaging is required in all cases to complete assessment and staging. (R) Magnetic resonance imaging is recommended for primary site and computed tomography scan for neck and chest. (R) Positron emission tomography combined with computed tomography scanning is recommended for the assessment of response after chemoradiotherapy, and has a role in assessing recurrence. (R) Examination under anaesthetic is strongly recommended, but not mandatory. (R) Histological diagnosis is mandatory in most cases, especially for patients receiving treatment with curative intent. (R) Oropharyngeal carcinoma histopathology reports should be prepared according to The Royal College of Pathologists Guidelines. (G) Human papilloma virus (HPV) testing should be carried out for all oropharyngeal squamous cell carcinomas as recommended in The Royal College of Pathologists Guidelines. (R) Human papilloma virus testing for oropharyngeal cancer should be performed within a diagnostic service where the laboratory procedures and reporting standards are quality assured. (G) Treatment options for T1–T2 N0 oropharyngeal squamous cell carcinoma include radical radiotherapy or transoral surgery and neck dissection (with post-operative (chemo)radiotherapy if there are adverse pathological features on histological examination). (R) Transoral surgery is preferable to open techniques and is associated with good functional outcomes in retrospective series. (R) If treated surgically, neck dissection should include levels II–IV and possibly level I. Level IIb can be omitted if there is no disease in level IIa. (R) If treated with radiotherapy, levels II–IV should be included, and possibly level Ib in selected cases. (R) Altering the modalities of treatment according to HPV status is currently controversial and should be undertaken only in clinical trials. (R) Where possible, patients should be offered the opportunity to enrol in clinical trials in the field. (G)